PERAN ORANG TUA MILENIAL DALAM MENDIDIK GENERASI ALPHA DI ERA DIGITAL - Adhatul Pitriyani; RR. Deni Widjayatri (QURROTI, 2022)
The development of technology from generation to generation continues to develop rapidly. Providing progress in every sector, one of which is in the education sector which has the impact of technological advances. With technological advances, it becomes a challenge for every parent in dealing with education for early childhood which is the alpha generation that grows and develops with the current technological advances. Advances in technology will cause a positive or negative impact on children's education, which basically children do not understand to look for good information or not because early childhood is a time when children are happy to explore everything, one of which is technology. The purpose of this study is to conduct a literature review on the role of millennial parents in educating the alpha generation in the digital era. This research uses a qualitative descriptive approach with a literature study method. The article comes from data based on google schoral published in the last 5 years period (2017-2021). The results of the study show that the role of millennial parents in educating the alpha generation in the digital era is very important. The alpha generation needs guidance and supervision in using technology and many millennial parents take part in activities such as kulwap, seminars and workshops on parenting in the digital era which aim to find out the needs of children to increase knowledge in appropriate parenting, and to create good child development.